2023
DOI: 10.1038/s41586-023-06639-8
|View full text |Cite|
|
Sign up to set email alerts
|

Intermediate conformations of CD4-bound HIV-1 Env heterotrimers

Kim-Marie A. Dam,
Chengcheng Fan,
Zhi Yang
et al.

Abstract: HIV-1 envelope (Env) exhibits distinct conformational changes in response to host receptor (CD4) engagement. Env, a trimer of gp120 and gp41 heterodimers, has been structurally characterized in a closed, prefusion conformation with closely associated gp120s and coreceptor binding sites on gp120 V3 hidden by V1V2 loops1–4 and in fully saturated CD4-bound open Env conformations with changes including outwardly rotated gp120s and displaced V1V2 loops3–9. To investigate changes resulting from substoichiometric CD4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…1-5). Recently, cryoET of Env in membranes by Li et al 15 unraveled the initial contact of Env with CD4, and cryoEM single particle analysis of engineered Env by Dam et al 14 Overall, our trajectory approach integrates Env dynamics and static structures, expanding our understanding of the structural features of Env trimers in the context of its transition process upon engagement with CD4 and the host (Supplementary Fig. 6).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…1-5). Recently, cryoET of Env in membranes by Li et al 15 unraveled the initial contact of Env with CD4, and cryoEM single particle analysis of engineered Env by Dam et al 14 Overall, our trajectory approach integrates Env dynamics and static structures, expanding our understanding of the structural features of Env trimers in the context of its transition process upon engagement with CD4 and the host (Supplementary Fig. 6).…”
Section: Discussionmentioning
confidence: 91%
“…Initially 178 trimers with complete gp120 and gp41 were collected and one was excluded due to computational modeling 35 (PDB: 3J70). In addition, ligand free HIV-1 Env trimer 19 (PDB: 4ZMJ), along with one and two CD4 bound HIV-1 Env trimers 14 (PDB: 8FYI, 8FYJ) were included, resulting in a total 180 PDBs participating in the analysis. All 180 PDBs were aligned with each time frame of transition pathway and RMSD analysis was performed using PyMOL (www.pymol.org).…”
Section: Collection Of Hiv-1 Env Trimers and Rmsd Analysis With The T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our mechanistic insights are partially based on structure of SOSIP Env. Although recent studies of SOSIP conformational changes were consistent with data driven form Envs on virions 50,57 , the use of SOSIP may have underestimated Env opening as this soluble format was originally engineered to capture closed, prefusion Env conformation. We analyzed symmetry of only two SOSIPs purified via Galanthus nivalis lectin under identical conditions; we expect that analysis of SOSIP Envs of additional HIV-1 strains, which are planned for future studies, will reveal a range of asymmetries that may relate to the ability of different Envs to “breathe”.…”
Section: Discussionmentioning
confidence: 96%
“…Several structural studies have shown CD4 molecules binding to an Env trimer can give different conformations of the trimer depending on whether one, two, or three CD4 molecules are bound, with the implication being that a trimer must be fully occupied with CD4 to allow the subsequent conformational changes to occur, leading to viral membrane fusion ( 8 , 40 42 ). Our modeling of infectivity as a function of surface CD4 density for R5 T-tropic viruses is consistent with this observation in that there is a strong dependence on surface CD4 density for infectivity implying the need to interact with multiple CD4 molecules.…”
Section: Discussionmentioning
confidence: 99%